A study on beneficial impact of the use of medium-molecular-weight hydroxyethyl starch in granulocyte apheresis using continuous-flow cell separator Spectra Optia: A retrospective single-center study at a tertiary care oncology center - Amardeep Pathak; Devasis Panda; Narender Tejwani; Anurag Mehta (Asian Journal of Transfusion Science)
INTRODUCTION: Granulocyte transfusion is one of the best therapeutic modalities in prolonged neutropenic patients with severe bacterial/fungal infections. Granulocyte harvest using conventional acid citrate dextrose (ACD) anticoagulant (ACD-A) by apheresis is not satisfactory in comparison to the use of hydroxyethyl starch (HES), but the latter is associated with various adverse events, especially with high-molecular-weight HES. AIMS AND OBJECTIVE: This study aimed to assess the beneficial impact of the use of medium-molecular-weight (MMW)-HES and trisodium citrate combination over ACD-A in granulocyte apheresis when using Spectra Optia. MATERIALS AND METHODS: This was a retrospective study comparing granulocyte harvest results with the use of ACD or HES and trisodium citrate combination. All the donors in both the groups received single 600 μg of granulocyte colony-stimulating factor subcutaneous injection followed by 8 mg of dexamethasone tablet 10–12 h and omnacortil 60 mg orally 3 h before harvest. A number of adverse incidents, if any, were observed and noted. Donor/procedure parameters were compared using Mann–Whitney U-test/unpaired t-test. RESULTS: Granulocyte yield (mean: 3.29 × 1010/unit vs. 4.5 × 1010/unit in the ACD and HES groups, respectively, P ≤ 0.0001) was significantly better in the HES group. The collection efficiency was also better in the HES group (mean: 15.86% vs. 26.70% in the ACD and HES groups, respectively, P ≤ 0.0001) in the ACD and HES groups, respectively. There was no significant adverse event noted in any of these two groups. CONCLUSION: In our study, granulocytes with optimum yield can be easily harvested with Spectra Optia cell separator using 6% HES (MMW) and trisodium citrate combination with standard 12-h interval gap between mobilization and harvest. This strategy can also have no or minimal extra cost burden to patients.